THE STUDY FOR THE ATTITUDE OF STUDENTS TOWARDS THE CHOSEN PROFESSION OF PHARMACIST - J. N. Grigoruk; N. S. Ponomarenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article examines the dynamics of students' attitude to the profession of pharmacist. Motivation factors for the choice of this profession were described. We have substantiated the stability of professional choice, and studied the satisfaction of students with the chosen profession.